Increasing community health worker productivity and effectiveness: a review of the influence of the work environment - Jaskiewicz Wanda; Tulenko Kate (BMC, 2012)
Abstract Background Community health workers (CHWs) are increasingly recognized as a critical link in improving access to services and achieving the health-related Millennium Development Goals. Given the financial and human resources constraints in developing countries, CHWs are expected to do more without necessarily receiving the needed support to do their jobs well. How much can be expected of CHWs before work overload and reduced organizational support negatively affect their productivity, the quality of services, and in turn the effectiveness of the community-based programmes that rely on them? This article presents policy-makers and programme managers with key considerations for a model to improve the work environment as an important approach to increase CHW productivity and, ultimately, the effectiveness of community-based strategies. Methods A desk review of selective published and unpublished articles and reports on CHW programs in developing countries was conducted to analyse and organize findings on the elements that influence CHW productivity. The search was not exhaustive but rather was meant to gather information on general themes that run through the various documents to generate perspectives on the issue and provide evidence on which to formulate ideas. After an initial search for key terminology related to CHW productivity, a snowball technique was used where a reference in one article led to the discovery of additional documents and reports. Results CHW productivity is determined in large part by the conditions under which they work. Attention to the provision of an enabling work environment for CHWs is essential for achieving high levels of productivity. We present a model in which the work environment encompasses four essential elements-workload, supportive supervision, supplies and equipment, and respect from the community and the health system-that affect the productivity of CHWs. We propose that when CHWs have a manageable workload in terms of a realistic number of tasks and clients, an organized manner of carrying out these tasks, a reasonable geographic distance to cover, the needed supplies and equipment, a supportive supervisor, and respect and acceptance from the community and the health system, they can function more productively and contribute to an effective community-based strategy. Conclusions As more countries look to scale up CHW programmes or shift additional tasks to CHWs, it is critical to pay attention to the elements that affect CHW productivity during programme design as well as implementation. An enabling work environment is crucial to maximize CHW productivity. Policy-makers, programme managers, and other stakeholders need to carefully consider how the productivity elements related to the work environment are defined and incorporated in the overall CHW strategy. Establishing a balance among the four elements that constitute a CHW's work environment will help make great strides in improving the effectiveness and quality of the services provided by CHWs.